Financial Inclusion, Poverty, and Income Inequality in Developing Asia - Cyn-Young Park; Rogelio Mercado (Asian Development Bank (ADB), 2015)
Poverty and income inequality remain a stubborn challenge in Asia and the Pacific despite the region's rapid economic expansion in previous decades, which lifted millions out of poverty. Financial inclusion is often considered as a critical element that makes growth inclusive as access to finance can enable economic agents to make longer-term consumption and investment decisions, participate in productive activities, and cope with unexpected short-term shocks. Understanding the link between financial inclusion, poverty, and income inequality at the country level will help policymakers design and implement programs that will broaden access to financial services, leading to reduction of poverty incidence and income equality. This paper extends the existing literature on financial inclusion by focusing on developing Asian economies. We construct our own financial inclusion indicator to assess various macroeconomic and country-specific factors affecting the degree of financial inclusion for 37 selected developing Asian economies. We also test the impact of financial inclusion, along with other control variables, on poverty and income inequality. Our results show that per capita income, rule of law, and demographic characteristics significantly affect financial inclusion in developing Asia. Furthermore, we find that financial inclusion significantly reduces poverty; and there is also evidence that it lowers income inequality. Our findings suggest that the provisions for young and old-age populations, e.g., retirement pensions; and stronger rule of law, including enforcement of financial contracts and financial regulatory oversight, will broaden financial inclusion, thereby contributing to poverty reduction and lower income inequality.
hdl:11540/2272
Keywords: G18; O11; O16; 330; developing Asia; financial inclusion; income inequality; poverty